Social Pedagogy in Russia: Trends, Problems, Ideas - Sorochinskaya, Elena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The given paper is concerned with holistic approach to social pedagogy in Russia. Itcovers the key trends in development of social pedagogy over the last 25 years. The main objective of the given paper is to give coverage to the researches that make significant contribution to development of social pedagogy in Russia. The author of the article highlights the key directions ofthe researches in the domain of social pedagogy,such as providing scientific grounds forthe new direction of pedagogical knowledge, creation and development of schools of thought in social pedagogy, specific features of socialization of a growing personality, content and techniques of professional social education.The author states that only studying positive experience is the way to solving the problems that modern social pedagogy faces nowadays.